Employment Opportunities for Graduates of Agricultural TVET Schools in Haiti - Christelle M. Calixte; Grady T. Roberts; J.C. Bunch (Journal of International Agricultural and Extension Education, 2019)
The literature suggests that in Haiti, the extension work is primarily conducted by graduates from agricultural TVET schools. However, Haiti is a country with alarming data for food insecurity and severe hunger index. This situation arises questions about the manner in which TVET contributes to the dissemination of best agricultural practices amongst farmers and the role that extension agents play in bringing the scientific discoveries into the rural communities. Moreover, little research has been made about the current situation of Haitian TVET within the agricultural system. This study used basic qualitative methods with a constructivist approach, and backwards design as theoretical framework to explore the employment of TVET graduates within the Haitian agricultural system. Schools’ directors and teachers were individually interviewed, and focus groups conducted with the students, which revealed the employers of TVET graduates, the types of jobs they realize within the system and the external factors that affect employment opportunities. Employers of technicians were most likely public sector, NGOs and IOs as well as entrepreneurship activities. These TVET graduates’ job profiles are in extension performing versatile work, or as entrepreneurs. Their employment opportunities were affected by the overall unemployment, the existing opportunities in agriculture, and lack of government support.
Keywords: Haiti; employment; technical schools; agriculture